Effects on walking of simultaneous upper/lower limb abobotulinumtoxina injections in patients with stroke or brain injury with spastic hemiparesis - Peter J. McAllister; Svetlana E. Khatkova; Steven G. Faux; Philippe Picaut; Romain Raymond; Jean-Michel Gracies (Medical Journals Sweden, 2019)
Objective: To compare walking speed in patients with spastic hemiparesis who received abobotulinumtoxinA either in the lower limb or simultaneously in both the lower and upper limbs. Design: Post hoc analysis from a phase 3 study of abobotulinumtoxinA (Dysport®, NCT01251367). Patients: Adult patients with spastic hemiparesis causing gait dysfunction. Methods: Comfortable barefoot walking speed over 10 m was evaluated in patients receiving lower limb vs lower and upper limb injections over ≤4 treatment cycles; 1,000 U or 1,500 U in lower limb for cycle 1/2; optional upper limb injections from cycle 3 (500 U: upper limb, 1,000 U: lower limb). Results: Mean (standard deviation; SD) lower limb cycle 3/4 doses were lower in the lower plus upper limb group vs lower limb only (1,000 U (SD 50), 1,000 U (SD 50) vs 1,380 U (SD 210), 1,360 U (SD 220). Baseline comfortable barefoot walking speed was similar between groups. Changes at cycle 3 week 4, in m/s, were: lower and upper limb: +0.063 (SD 0.131); lower limb only: +0.078 (SD 0.114), and cycle 4 week 4: lower and upper limb: +0.086 (SD 0.166); lower limb only: +0.086 (SD 0.123). Conclusion: Simultaneous lower and upper limb abobotulinumtoxinA treatment does not hamper improvement in walking speed compared with lower limb treatment alone. Thus, physicians may split the 1,500 U abobotulinumtoxinA dose as needed to best treat patients with spastic paresis.